1999
DOI: 10.1063/1.371678
|View full text |Cite
|
Sign up to set email alerts
|

Spin-polarized tunneling in a half-metallic ferromagnet

Abstract: Direct measurement of the conduction electron spin polarization ͑P͒ in epitaxial NiMnSb was performed to test the prediction of half metallicity in this material. Spin-polarized tunneling in NiMnSb/Al 2 O 3 /Al junctions showed P of 28%, contrary to the predicted value of 100%. Magnetoresistance measurements in NiMnSb/Al 2 O 3 /Ni 80 Fe 20 junctions concurred with this result. The discrepancy between theory and experiment is discussed. Also, the latter junctions show four nonvolatile remanent states due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
92
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(97 citation statements)
references
References 19 publications
5
92
0
Order By: Relevance
“…These polarisation values are consistent with a small perpendicular magnetoresistance measured for NiMnSb in a spin-valve structure [23], and a superconducting and a magnetoresistive tunnel junction [5]. Ristoiu et al showed that during the growth of the NiMnSb thin films, first Sb and then Mn atoms segregate to the surface, which is far from being perfect, thus decreasing the obtained spin-polarization [24].…”
Section: Introductionsupporting
confidence: 79%
“…These polarisation values are consistent with a small perpendicular magnetoresistance measured for NiMnSb in a spin-valve structure [23], and a superconducting and a magnetoresistive tunnel junction [5]. Ristoiu et al showed that during the growth of the NiMnSb thin films, first Sb and then Mn atoms segregate to the surface, which is far from being perfect, thus decreasing the obtained spin-polarization [24].…”
Section: Introductionsupporting
confidence: 79%
“…ferromagnets with full spin polarization at the Fermi levelare promising materials for applications in spintronics [11,12]. They can be employed as spin filters [13], in spin injection/detection devices [14,15] or in magnetic tunnelling junctions (MTJs) [16]. Apart from a few oxidic compounds and Mn-doped semiconductors [17][18][19], the class of Heusler alloys provides the only metallic alloy system with halfmetallicity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most interesting problems of this new field is the spin-injection from a ferromagnet into a semiconductor, that would lead to the creation of efficient spin-filters [3], tunnel junctions [4], GMR devices for spin injection [5], etc. This has intensified the interest in the so-called half-ferromagnetic materials which have a band gap at the Fermi level (E F ) for one spin direction and thus exhibit 100% spin polarisation at E F .…”
Section: Introductionmentioning
confidence: 99%